Association of Mutations in Toll-like Receptor 2 Signaling Genes With Fulminant Form of Hepatitis B–Related Acute Liver Failure. (21st February 2017) - Han, Yue; Gu, Leilei; Liu, Jing; Li, Xinhua; Wang, Mingjie; Gong, Qiming; Yu, Demin; Yang, Zhitao; Zhang, Donghua; Yang, Huijuan; Shen, Zhongliang; Zhu, Hongguang; et al.
Abstract: Background: The fulminant form of hepatitis B–related acute liver failure (FHB-ALF) is a rare but highly fatal outcome of acute hepatitis B virus (HBV) infection. Its related host factors have not been studied to our knowledge. Methods: To identify functionally relevant biological pathway(s) in FHB-ALF pathogenesis, pathway enrichment analysis was conducted on a data set of rare case-specific variants derived from exomic sequencing of 10 unrelated cases. Key variants in identified pathways were validated using 312 controls with HBV disease. Mechanistic studies of a recurrent Toll-like receptor (TLR) 2 gene ( TLR2 ) variant were performed in vitro and in vivo. Results: The TLR signaling pathway was highly enriched, with associated variants found in 9 of the 10 cases. Notably, a rare heterozygous single-nucleotide variation causing F679I mutation in TLR2 was identified in 2 unrelated cases. In vitro analysis demonstrated F679I to cause loss of function. In both heterozygous and homozygous TLR2 knockout mice, injection of HBV replicon plasmid resulted in more prominent alanine aminotransferase elevations and hepatic necroinflammation than in wild-type mice. Mechanistic analyses demonstrated reduced regulatory T-cell percentages in postexposure TLR2 knockout mice. Conclusions: TLR2 signaling is very likely impaired in patients with FHB-ALF. The recurrence of rare case-specific TLR2 variant strongly suggests mechanistic contribution to fulminancy in HBV infection. Summary: Exome sequencing and pathway enrichment analysis followed by functional characterizations associated with host genetic variations causing impairment of the Toll-like receptor 2 signaling pathway with pathogenesis of fulminant form of hepatitis B–related acute liver failure.